SISTEM INFORMASI GEOGRAFIS PEMETAAN LAHAN PERTANIAN DAN KOMODITI HASIL PANEN KABUPATEN KUDUS - Susanto, Arief; Kharis, Ahmad; Khotimah, Tutik (Jurnal Informatika, 2016)
Along with advances in computer technology and information today, GIS (Geographic Information System) technology is being developed both desktop and online. many government agencies and companies that utilize the GIS technology to collect data on a regional and a record of its assets, such as soil data, the data region and others. One of the companies or the Department requiring that the Department of Agriculture, Fisheries and Forestry Kudus Regency, because there is no agricultural land mapping and data collection on commodity crops at the area. With the system, the Department of Agriculture, Fisheries and Forestry Kudus Regency become more efficient, fast and complete to log the results of commodity crops and have a local mapping data in Kudus regencys, and with computerized systems online, then the Department would be easier to record an area with more quickly and anywhere. The method used to design the system that is using the Waterfall method by Sammerville Ian. The results of the research that will be generated by the system is to facilitate the Department of Agriculture, Fisheries and Forestry Kudus Regency to find out the results of Commodities at a sub-district or village.Â Keywords: GIS, Harvest Commodities, agricultural commodities